2013
DOI: 10.1021/ol401610e
|View full text |Cite
|
Sign up to set email alerts
|

Iridium-Catalyzed Hydrogen Transfer: Synthesis of Substituted Benzofurans, Benzothiophenes, and Indoles from Benzyl Alcohols

Abstract: An iridium-catalyzed hydrogen transfer has been developed in the presence of p-benzoquinone, allowing the synthesis of a diversity of substituted benzofurans, benzothiophenes, and indoles from substituted benzylic alcohols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The borrowing hydrogen methodology involves (1) oxidation of alcohols or ammonia to the corresponding carbonyl compounds or imines; (2) alkylation of ketones, alcohols, or amines to form unsaturated carbonyl compounds or imines; and (3) reduction of the C–C or C–N bonds using the borrow hydrogen atoms from alcohols or amines (Scheme ). , Generally, among these transformations, the catalyst plays a crucial role in every step. To date, although some metals (Pd, Au, Ag, Cu, Fe, Ni, Os, and Rh,) have been studied, Ru and Ir are still shown to be the most effective and promising catalysts for C-alkylation and N-alkylation.…”
Section: Introductionmentioning
confidence: 99%
“…The borrowing hydrogen methodology involves (1) oxidation of alcohols or ammonia to the corresponding carbonyl compounds or imines; (2) alkylation of ketones, alcohols, or amines to form unsaturated carbonyl compounds or imines; and (3) reduction of the C–C or C–N bonds using the borrow hydrogen atoms from alcohols or amines (Scheme ). , Generally, among these transformations, the catalyst plays a crucial role in every step. To date, although some metals (Pd, Au, Ag, Cu, Fe, Ni, Os, and Rh,) have been studied, Ru and Ir are still shown to be the most effective and promising catalysts for C-alkylation and N-alkylation.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of transition-metal catalysts well-known to be highly active in hydrogen autotransfer reactions, including Pd/C, RuCl 2 (PPh 3 ) 3 , [Ir­(cod)­Cl] 2 , [Ir­(coe) 2 Cl] 2 , [Ir­(OMe)­(cod)] 2 , and RuHCl­(CO)­(PPh 3 ) 3 , were screened. We found that the iridium dimer [Cp*IrCl 2 ] 2 was the most efficient catalyst. After 48 h, we observed complete consumption of the indole and selective formation of the desired N -acetyltryptamine (35% yield; Table , entry 9), without traces of the N 1 -alkylated product.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Therefore, a number of syntheses have been developed to date [1,2]. Representative methods for the construction of simple, unsubstituted benzothiophenes are categorized into several approaches (Scheme 1): (i) Hinsberg-type annulations [7][8][9], (ii) Friedel-Crafts type annulations [10][11][12][13], (iii) Wittig-type condensations of phosphonium salts [14,15], (iv) Metal-catalyzed thiolation annulations [16][17][18], (v) Pd-catalyzed C-H arylations [19], and others [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%